Consumption of fashionable clothing brands: an exploratory study of fashion purchases by South African teenage girls - Kolane, Lipalesa Didi (My University, 2016)
The purpose of this research paper is to explore the proposition around the factors influencing fashion choices for teenage girls which include attitude, impulse consumption, peer pressure, self-congruency and socialisation agents which all lead to their intention to purchase fashionable clothing brands. The research problem was to identify whether the factors influencing teenagers’ attitudes and decision making styles actually affect their intention to consume fashionable clothing brands. The design approach and methodology was the gathering of qualitative data from conducting five focus groups consisting of six female respondents each. The respondents were teenage girls aged between 13 and 19 years old, from different social backgrounds. Findings showed relatively high levels of consumption of fashion brands among the respondents, but not necessarily conducted in the traditional consumer decision-making processes. The manner in which teenage girls consume fashion brands creates a clear distinction and gap in the market of how to connect with this age segment. Key findings of the research show that teenagers no longer conform to typical adolescent ways, and it is through their consumption behaviour that marketers need to identify ways in which retail marketers can engage with them.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (August 2016)
Keywords: Consumer behavior--South Africa; Teenage girls--South Africa; Clothing trade--South Africa; Brand choice--South Africa